Restoration of converging implants: Restorative complexity to facilitate retrievability - James Dudley (Wolters Kluwer Medknow Publications, 2020)
Implant treatment should be restoratively driven, however at times, ideal implant positioning may be sacrificed for surgical convenience at the expense of restorative complexity. A prosthesis incorporating a novel design was constructed to restore two converging implants placed in close proximity utilizing standard implant impression componentry and simple clinical stages. As the use of angulated screw channel technology was not possible, a customized cast "rest" abutment and overlying telescopic crown was fabricated that facilitated access for oral hygiene and retrievability as required. The complexity of the case design was transferred to the laboratory phases of construction. The case presented a satisfactory clinical outcome for an initially challenging implant presentation and reinforced the need to work closely with the laboratory technician.